2018
DOI: 10.1017/s0033291718002489
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability during a cognitive reappraisal task in female patients with borderline personality disorder: the role of comorbid posttraumatic stress disorder and dissociation

Abstract: Findings suggest increased emotional reactivity to negative, positive, and neutral pictures, but do not provide evidence for deficits in instructed ER in BPD. Reduced HF-HRV appears to be particularly linked to comorbid PTSD, while dissociation may underlie attempts to increase ER and HF-HRV in BPD patients with this comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 94 publications
5
37
1
1
Order By: Relevance
“…In another study by Krause-Utz and colleagues [ 125 ••], high-frequency heart rate variability (HF-HRV, i.e., a marker of stress regulation) was investigated during an emotion regulation task in female BPD patients with versus without comorbid PTSD and healthy women. Participants were instructed to either attend or downregulate emotional responses to neutral, positive, and negative images.…”
Section: Other Recent Research On Dissociation In Bpdmentioning
confidence: 99%
“…In another study by Krause-Utz and colleagues [ 125 ••], high-frequency heart rate variability (HF-HRV, i.e., a marker of stress regulation) was investigated during an emotion regulation task in female BPD patients with versus without comorbid PTSD and healthy women. Participants were instructed to either attend or downregulate emotional responses to neutral, positive, and negative images.…”
Section: Other Recent Research On Dissociation In Bpdmentioning
confidence: 99%
“…With regard to the effect of regulation strategies on affect, we predicted that the negative effect of rumination on affect is more pronounced in both, individuals with BPD or MDD when compared to healthy individuals. Based on recent findings (e.g., Krause-Utz et al, 2019) and contrary to the preregistration, we did not expect any group differences in the effect of RUNNING HEAD: AFFECT REGULATION IN BPD AND MDD -10 -reappraisal on affect. Finally, we predicted that suppression is effective in reducing negative affect only in individuals with BPD.…”
Section: Introductionmentioning
confidence: 72%
“…In the present study, we revealed reduced sympathetic-related HRV in individuals with PTSD + DS as compared to controls. Indeed, prior investigations have demonstrated a positive relationship between parasympathetic nervous system (PNS) activity and dissociation in response to threatening cues in other clinical populations, thus pointing to a close relationship between sympathoinhibition and dissociative symptomatology ( Farina et al, 2015 ; Fitzpatrick and Kuo, 2015 ; Chou et al, 2018 ; Schäflein et al, 2018 ; Krause-Utz et al, 2019 ). Specifically, dissociation has been associated with parasympathetic overactivation, which has been thought to be linked to emotional detachment as expressed by symptoms of emotional numbing, depersonalization, and derealization (for an overview see Schauer and Elbert, 2015 ; Lanius et al, 2018 , 2020 ; Terpou et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these contrasting findings may be driven partially by dissociative symptomatology. Several studies examining the relationship between dissociation and HRV in different populations have reported enhanced recruitment of the PNS in response to threatful or trauma-related cues, thus pointing toward a relationship between dissociation and sympathoinhibitory responses ( Farina et al, 2015 ; see also Owens et al, 2015 ; Chou et al, 2018 ; Schäflein et al, 2018 ; Herzog et al, 2019 ; Krause-Utz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%